Foreign Food Plants as Prestigious Gifts: The Archaeobotany of the Amarna Age Palace at Tel Beth-Shemesh, Israel - Weiss, Ehud (Bulletin of ASOR, 2019)
In contrast with the relatively rich documentation from the el-Amarna archive related to the main city-states of the southern Levant in the Amarna Age (Late Bronze Age IIA; 14th century b.c.e.), archaeological data from these sites is still wanting. This unfortunate situation highlights the importance of the ca. 60,000-item plant collection from the recently exposed Late Bronze Age IIA palace at Tel Beth-Shemesh. Room L1505 in the palace-apparently a pantry due to its contents of foodstuffs and vessels for food preparation and consumption-contained eight deposits of carbonized crop plants. Deposits of almost pure grains and very low numbers of weed seeds were found, indicating that these stored food plants were ready to be used in food preparation. Of special interest is the presence of a sizeable amount of two rare pulses in Levantine archaeobotany-fenugreek (Trigonella foenum-graecum) and Cyprus vetch (Lathyrus ochrus)-only found in two other Bronze Age royal contexts: Tutankhamun's tomb in Egypt and the Late Minoan II Unexplored Mansion in Knossos. Thus, in addition to attesting to the agricultural practices and culinary preferences of a Canaanite ruling court during the Amarna Age, this botanical assemblage also hints at prestigious royal gift exchanges of exotic food plants.